After the War - 'The Plebs', 1943 (1943)
1943 1939-1945 "After the War - 'The Plebs', 1943" [HFR0071], 1943 The front page from the November 1943 issue of The Plebs magazine, published by the National Council of Labour Colleges, illustrates the optimism felt in the radical and labour movements about the possibilities for changes in society in the post war world. The cartoon is from Socialist Appeal, the newspaper of the Trotskyist Workers International League.